On Impulsive Sequential Fractional Differential Equations (ISFDE’s) - Ghadaireh, Bilal Sami Mohammad (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
In this thesis, we study the existence and uniqueness of a nonlinear impulsive sequential fractional differential equations of order 1,2 involving Liouville-Caputo fractional derivative supplemented with the separate boundary value conditions. The subject of boundary value problem and fractional differential equations are very important in many fields of science and engineering. In fact, both sequential fractional differential equations and Impulsive fractional differential equations are studied individually from various perspectives. However, this topic combining both of them to produce a wider case namely, impulsive sequential fractional differential equations. By doing so, a new existence and uniqueness results of solutions are provided for the problems. Keywords: Nonlinear impulsive sequential fractional differential equations, Caputo fractional derivative, Banach fixed point theorem.

ÖZ: Bu tezde, ayrı sınır-değer koşullarıyla desleklenmiş, Liouville-Caputo kesirli türevi içeren, mertebeli doğrusal olmayan Impılsif sıralı kesirli diferansiyel denklemlerin varlık ve tekliği çalışılacaktır. Sınır-değer problemleri ve kesirli diferansiyel denklemler, temel bilimler ve mühendisliğin birçok alanında çok büyük önem taşımaktadır. Hem sıralı kesirli diferansiyel denklemler hem de impulsif kesirli diferansiyel denklemler ayrı ayrı farklı perspektiflerden çalışılmıştır. Ancak, bu iki tip diferansiyel denklemin birleştirilmesiyle elde edilen ve daha geniş bir sınıf oluşturan impulsif sıralı kesirli diferansiyel denklemler sadece bu tezde çalışılmıştır. Bu çalışmada, bu özel tipteki diferansiyel denklemlerin çözümü için yeni varlık ve teklik sonuçları elde edilmiştir. Anahtar Kelimeler: doğrusal olmayan impulsif sıralı kesirli diferansiyel denklemler, Caputo kesirli türevi, Banach Sabit nokta teoremi.
Doctor of Philosophy in Mathematics. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Mathematics, 2018. Supervisor: Prof. Dr. Nazim Mahmudov.
Keywords: Mathematics; Boundary value problems--Differential equations; Fractional differential equation, sequential; Nonlinear impulsive sequential fractional differential equations; Caputo fractional derivative; Banach fixed point theorem